2005
DOI: 10.5194/bg-2-113-2005
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from Indian rice fields: calibration and upscaling using the DNDC model

Abstract: Abstract. The Denitrification and Decomposition (DNDC) model was evaluated for its ability to simulate methane (CH 4 ), nitrous oxide (N 2 O) and carbon dioxide (CO 2 ) emissions from Indian rice fields with various management practices. The model was calibrated and validated for field experiments in New Delhi, India. The observed yield, N uptake and greenhouse gas (GHG) emissions were in good agreement with the values predicted by the model. The model was then applied for estimation of GHG emissions from rice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(75 citation statements)
references
References 44 publications
3
72
0
Order By: Relevance
“…The geographical distribution of the emissions is assessed by global (USEPA, 2006(USEPA, , 2012EDGARv4.2FT2010, 2013 and regional Chen et al, 2013;Chen and Prinn, 2006;Yan et al, 2009;Castelán-Ortega et al, 2014; inventories or by land surface models (Spahni et al, 2011;Zhang and Chen, 2014;Ren et al, 2011;Tian et al, 2010Tian et al, , 2011Li et al, 2005;Pathak et al, 2005). The emissions show a seasonal cycle, peaking in the summer months in the extratropics associated with the monsoon and land management.…”
Section: Rice Cultivationmentioning
confidence: 99%
“…The geographical distribution of the emissions is assessed by global (USEPA, 2006(USEPA, , 2012EDGARv4.2FT2010, 2013 and regional Chen et al, 2013;Chen and Prinn, 2006;Yan et al, 2009;Castelán-Ortega et al, 2014; inventories or by land surface models (Spahni et al, 2011;Zhang and Chen, 2014;Ren et al, 2011;Tian et al, 2010Tian et al, , 2011Li et al, 2005;Pathak et al, 2005). The emissions show a seasonal cycle, peaking in the summer months in the extratropics associated with the monsoon and land management.…”
Section: Rice Cultivationmentioning
confidence: 99%
“…The major models that are able to simulate CH 4 production include MEM (Cao et al, 1995a), MERES (Matthews et al, 2000), InfoCrop (Aggarwal et al, 2004), DNDC (Li et al, 1992a) and so on. In recent years, these models played an important role in describing CH 4 production and oxidation process in paddies and estimating the CH 4 emissions at regional or global scales (Cao et al, 1995b(Cao et al, , 1996Bachelet and Neue, 1993;Li et al, 2004;Pathak et al, 2005;Zhang et al, 2009a). Among the candidate models, DNDC has been tested for the rice paddies in China and other Asian countries.…”
Section: Y Zhang Et Al: Quantifying Methane Emissions From Rice Padmentioning
confidence: 99%
“…Many long-term field experiments have indicated that proper fertilization together with straw return can increase soil organic carbon (SOC) content (Huang and Sun, 2006;Mosier et al, 2006;Zhang et al, 2010;Shang et al, 2011). However, these practices may also stimulate N 2 O emissions by increasing the supply of substrates for soil nitrifiers and denitrifiers, and the resulting increase in microbial activity may offset the SOC sequestration effects (Pathak et al, 2005). Field practices that change some soil conditions to mitigate one form of GHG emissions may bring about favourable conditions for other forms of emissions and thereby change the overall balance of GHGs (Pathak et al, 2005;Shang et al, 2011;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, these practices may also stimulate N 2 O emissions by increasing the supply of substrates for soil nitrifiers and denitrifiers, and the resulting increase in microbial activity may offset the SOC sequestration effects (Pathak et al, 2005). Field practices that change some soil conditions to mitigate one form of GHG emissions may bring about favourable conditions for other forms of emissions and thereby change the overall balance of GHGs (Pathak et al, 2005;Shang et al, 2011;Ma et al, 2013). To measure these overall effects in any given system the concept of net global warming potential (NGWP) was proposed based on the radiative properties of all the GHG emissions and carbon fixation, expressed as CO 2 -eq ha −1 yr −1 , to give an integrated evaluation of whether the system is positive or negative in terms of CO 2 -eq (Robertson and Grace, 2004).…”
Section: Introductionmentioning
confidence: 99%